Persepsi Wisatawan Domestik Terhadap Desa Wisata Religi Bubohu Bongo Kabupaten Gorontalo - Talib, Desrika; Lagalo, Anggraeni M.S; Talib, Boby H. (Tulisan Ilmiah Pariwisata (TULIP), 2023)
The Religious Tourism Village of Bubohu Bongo is one of the tourist destinations in the Gorontalo Province and is a sought after destination due to its ancient religious ceremony tradition, namely the implementation of walima conducted every Maulid of Prophet Muhammad SAW. The traditions and rituals held by the Religious Tourism Villageof Bubohu Bongohave long been evolving and attract tourist in searchof something authentic. This research aims to determine Tourist Perceptions of the Bubohu Bongo Religious Tourism Village, Gorontalo Regency. The method used  is a quantitative study with a cross sectional approach. The sampling technique used was accidental sampling with a sample of 30 respondents. Data collection uses a questionnaire sheet. From the results of statistical tests using the Chi Square test, it was obtained a P-value of 0.003 where <0.05 was a significant level, so that Ha was accepted and H0 was rejected and it can be concluded that there is a relationship between tourist perceptions of the tourist attraction of the Bubohu Bongo Religious Tourism Village.